Umphred's neurological rehabilitation - Umphred, Darcy Ann (Elsevier Mosby, 2013)
Using a problem-solving approach based on clinical evidence, Neurological Rehabilitation, 6th Edition covers the therapeutic management of people with functional movement limitations and quality of life issues following a neurological event. It reviews basic theory and covers the latest screening and diagnostic tests, new treatments, and interventions commonly used in today's clinical practice. This edition includes the latest advances in neuroscience, adding new chapters on neuroimaging and clinical tools such as virtual reality, robotics, and gaming. Written by respected clinician and physical therapy expert Darcy Umphred, this classic neurology text provides problem-solving strategies that are key to individualized, effective care.
Keywords: Nervous System Diseases; rehabilitace; Rehabilitation; rehabilitační a fyzikální medicína; nemoci nervového systému; neurologie